2022
DOI: 10.1371/journal.pone.0262331
|View full text |Cite
|
Sign up to set email alerts
|

The association of sleep duration and quality with depressive symptoms in older Chinese women

Abstract: Poor sleep quality or short and long sleep duration are associated with many negative health outcomes, such as diabetes, hypertension, and fatigue, which may directly or indirectly correlate with poor mental health. Although, the association between sleep duration and quality, and depressive symptoms has been examined, the results of these studies were inconsistent and evidence specifically on older women is lacking. Therefore, we designed a cross-sectional study to evaluate the association between sleep durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…The close relationship between sleep duration and depression and anxiety is previously demonstrated 31 35 . Interestingly, here we found a significant 45% increased odds ratio of SSD (< 6 h) associated with depression and a 96% increased odds ratio of LSD (> 9 h) in Thyroid diseases, only in the HDU group, and these associations were not significant in the NHDU group.…”
Section: Discussionmentioning
confidence: 63%
“…The close relationship between sleep duration and depression and anxiety is previously demonstrated 31 35 . Interestingly, here we found a significant 45% increased odds ratio of SSD (< 6 h) associated with depression and a 96% increased odds ratio of LSD (> 9 h) in Thyroid diseases, only in the HDU group, and these associations were not significant in the NHDU group.…”
Section: Discussionmentioning
confidence: 63%
“…A meta-analysis including 34 prospective studies identified a positive relationship between insomnia symptoms and depression symptoms, the pooled RR was 2.27 [ 15 ]. A cross-sectional study of older women over 60 in Shanghai showed that poor sleep quality increases the risk of normal depression symptoms [ 14 ]. A co-twin control study showed that depressive symptoms were associated with several objectively measured indices of sleep disturbance [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were several cross-sectional and prospective studies on the relationship between insomnia symptoms and depression symptoms [ 7 , 14 16 ], few studies have further analyzed the association between insomnia symptoms and depressive symptoms in adults by gender and age. Epidemiological studies have consistently shown a higher prevalence of insomnia symptoms and short sleep duration among women compared to men [ 17 ], while the rate of short sleep duration increases with age [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Statistics related to sleep disorders say that 30% -48% of the elderly experience insomnia (18). The prevalence of insomnia occurs more in the elderly than the young (19). Insomnia is characterized by the inability to initiate sleep, maintain sleep, wake up too early or sleep that is not refreshing.…”
Section: Sleep Disturbance In Elderlymentioning
confidence: 99%